An overview of glycopyrrolate/eFlow® CS in COPD. (3rd June 2018) - Kerwin, Edward; Ferguson, Gary T.
ABSTRACT: Introduction : COPD is highly prevalent in the US and globally, requiring new treatment strategies due to the high disease burden and increase in the aging population. Here, we profile the newly FDA-approved LONHALA MAGNAIR (glycopyrrolate [GLY]/eFlow® Closed System [CS]; 25 mcg twice daily), a nebulized long-acting muscarinic antagonist (LAMA) for the long-term maintenance treatment of COPD, including chronic bronchitis and/or emphysema. Areas covered : An overview of COPD and treatment landscape, focusing on GLY/eFlow CS, reviewing the published literature pertinent to the drug/device combination is reported. Expert commentary : GLY/eFlow CS consists of glycopyrrolate delivered via a novel electronic nebulizer and is the first nebulized LAMA to be approved by the FDA. GLY/eFlow CS has been studied in an extensive clinical development program, including phase II dose-ranging studies, two 12-week phase III studies demonstrating statistically significant and clinically important improvements in pulmonary function and patient-reported outcomes with a well-tolerated safety profile, and a 48-week phase III study highlighting the long-term safety of GLY/eFlow CS, along with long-term improvements in lung function and patient-reported outcomes. Additional studies are required to assess the impact of GLY/eFlow CS on COPD exacerbations, identify alternative uses of the eFlow CS nebulizer, and direct comparisons to other LAMAs.